Sick and (Still) Broke: Why the Affordable Care Act Won't End Medical Bankruptcy - Ryan Sugden (Washington University Journal of Law & Policy, 2012)
In Part I of this Note, I begin with an examination of medical bankruptcy in America and analyze the factors and variety of medical expenses that cause an individual or family to file for bankruptcy. Part II briefly outlines the country's private health insurance industry and how variations in health coverage schemes affect a consumer‘s financial liability. I note that in the years leading up to the Affordable Care Act, insurers have increasingly injected market-based principles into health coverage thereby shifting greater financial liability onto consumers. In Part III, I turn to the recently enacted Affordable Care Act, focusing on the two primary ways that it seeks to improve the affordability of health insurance for consumers: (1) subsidies that reduce premium payments and out-of-pocket expenses and (2) strong regulations of all new health insurance plans. In Part IV, I analyze whether and to what extent the Affordable Care Act will affect medical bankruptcy, arguing that while the Act shelters citizens from catastrophic medical expenses—protection that will reduce the overall number of debtors—it will not completely eliminate medical bankruptcy. Instead, I suggest that the Affordable Care Act will accelerate the use of deductibles and out-of-pocket expenses to reduce rising medical costs. Because these market-based tools require that consumers be penalized for their poor financial and health decisions, a limited number of bankruptcies should be expected. The measure of the Affordable Care Act's success, therefore, should be measured by its ability to improve the affordability of care and not whether it completely eliminates medical bankruptcy.
Keywords: Bankruptcy; Health care costs; Patient Protection and Affordable Care Act; United States